Diagnostic Utility of Molecular Analysis in Cutaneous T-Cell Lymphoma: Tunisian Series on Clonality of TCRG Gene Rearrangement - Klai, Sarra; Helal, Imen; Jouini, Raja; Hammami, Houda; Kharrat, Maher; Fenniche, Sami; Khanchel, Fatma; Chadli-Debbiche, Aschraf (South Asian Journal of Cancer, 2025)
The diagnosis of cutaneous T-cell lymphoma (CTCL) is sometimes difficult. Detection of monoclonal T-cell receptor gamma (TCRG) gene rearrangement by polymerase chain reaction (PCR) has become an important adjunct to the diagnosis of CTCL. This study was designed to explore the concordance in terms of the diagnostic value of BIOMED-2 TCRG PCR protocol with the histological diagnosis.Confirmed and doubtful CTCLs were included in this descriptive cross-sectional study performed in the Habib Thameur Hospital in 2021. These cases were followed in the department of dermatology from 2012 to 2021. PCR tests were performed with TCRG BIOMED-2 clonality methods followed by capillary electrophoresis and GeneScan analysis. Clonality and statistical results were analyzed.Monoclonality was identified in 51% of confirmed CTCL cases (16/28 cases with confirmed mycosis fungoides and 2/7 other CTCL cases) and in 63% of doubtful cases, which were converted to malignant diagnosis. The results of TCRG clonality demonstrated a significant correlation with histopathology diagnoses of specimens. A moderate concordance was found between histology and molecular clonality.Results from this molecular clonality emphasize the importance of interpreting data in association with histopathological features of the lesions.
Keywords: cutaneous T-cell lymphoma; mycosis fongoides; clonality; TCRG; BIOMED-2 protocol; histology